2013
DOI: 10.3402/qhw.v8i0.21355
|View full text |Cite
|
Sign up to set email alerts
|

The experience of acculturative stress-related growth from immigrants’ perspectives

Abstract: Previous literature has mainly focused on the positive effects of stress associated with disability and illness, called stress-related growth. Little research has explored positive changes as a result of acculturative stress among a group of immigrants. In particular, older Asian immigrants may experience a high level of stress related to acculturation because they may face more challenges to adapt to and navigate a new culture. This study was designed to capture the characteristics of stress-related growth as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Leisure scholars demonstrate that leisure contributes to substantial health benefits, such as physical, psychological, cognitive, and social benefits, among older adults (Kim, Yamada, Heo, and Han, 2014; Kim & Kim, 2013; Mannell, 2007). The findings of this study are aligned with that of previous studies in that through leisure participation older Korean immigrants obtained health benefits, such as psychological well-being and social benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leisure scholars demonstrate that leisure contributes to substantial health benefits, such as physical, psychological, cognitive, and social benefits, among older adults (Kim, Yamada, Heo, and Han, 2014; Kim & Kim, 2013; Mannell, 2007). The findings of this study are aligned with that of previous studies in that through leisure participation older Korean immigrants obtained health benefits, such as psychological well-being and social benefits.…”
Section: Discussionmentioning
confidence: 99%
“…A body of leisure literature shows evidence that leisure engagement has been associated with positive outcomes, such as decreased levels of depression and stress (Chang, 2014; Fernández-Fernández, Márquez-González, Losada-Baltar, & Romero-Moreno, 2014), acculturation-related personal growth (Kim & Kim, 2013), and increased health perception (Chang, Yu, & Jeng, 2014). The primary contributor to these positive outcomes can be the ability of leisure to provide rich opportunities for older adults to socialize with others, ameliorate negative psychological symptoms, and increase physical ability.…”
Section: Leisure Benefits Among Older Asian Immigrantsmentioning
confidence: 99%
“…Keeping in mind the fact that acculturation can co‐exist with acculturative stress, it was of interest to explore the ways in which these two variables are associated with employment status. Recent investigations suggest that even though acculturation and personal resources and strengths assist in securing a job, attainment of a job could itself create stress (Jasinskaja‐Lahti & Liebkind, ; Kim & Kim, ; Nillar, ).…”
Section: Aim Of the Present Studymentioning
confidence: 99%
“…Along with the popularity of personal growth and meaning-focused coping research (Lancaster & Carlson, 2015;Markman et al, 2013), meanings gained from leisure appear to play a key role in adaptation to life stress. Recently, Kim and Kim's (2013) interview study with older Korean immigrants (n = 13) to the northwestern USA found that engagement in meaningful leisure activities (e.g., Korean traditional games, volunteer activities) helped them cope with acculturative stress by fostering a sense of belonging/ connectedness and promoting happiness and psychological wellbeing. According to MataCodesal, Peperkamp, and Tiesler (2015), the meaningfulness of leisure for migrants goes beyond issues of coping and adapting, and also involves issues of self-realization and selfexpression.…”
Section: Coping and Meaning-making Within Cultural Contextsmentioning
confidence: 99%